Relationship between obesity and periodontal disease: A literature review - Girano Castaños, Jorge (2020)
Obesity is a disease whose prevalence is on the rise. It does not discriminate in terms of gender or age, and is often considered a risk factor for different systemic diseases. It is also considered a progressive disease that affects not only the general health but also the quality of life of individuals. Several studies have reported that obesity may also be related to oral diseases as a result of a physiological alteration of the body that affects the soft tissues of the oral cavity, which is evidenced by clinical signs of periodontal inflammation. The main objective of this review article is to evaluate the relationship between obesity and periodontal disease. To this end, previously published studies that determine the relationship between both diseases were searched. This review presents several articles that show a possible relationship between both diseases. The intervention of inflammatory mediators in obesity could have a periodontal impact. Based on the available evidence, it is concluded that there is a possible relationship between periodontal disease and obesity.